PETSCII – A Character Set and a Creative Platform - Reunanen, Markku; Heikkinen, Tero; Carlsson, Anders (Replay. The Polish Journal of Game Studies, 2018)
PETSCII is the built-in character set used on 8-bit Commodore computers, such as the PET, C-64 and Plus/4. The character set and the BASIC environment provided an entry point to rudimentary graphic editing for a generation of hobbyists. Over the years PETSCII has been used for a variety of creative purposes: for example games, demos, telecommunications, videos, books and fine art have been created using the graphical symbols. Through the analysis of existing art works and our own hands-on project – a graphics editor – we dig deeper into the specific properties of the character set. In this article we show how the fixed symbols set the frame for what is possible and how, on the other hand, they provide grounds for creative experimentation, display of skill and recognizable styles.